THE VALUES OF ISLAMIC EDUCATION IN THE READING BARZANJI TRADITION AT NEGERI LIANG MOLUCCAS - Nuria Nuria Nuria; Yusuf Abdurrahman Luhulima; Hayati Nufus Nufus (IAIN Ambon, 2022)
This research aims to determine the values of Islamic education contained in the Barzanji Reading Tradition so that there is no culture or custom that is misinterpreted by the community which leads to polytheism. The method used in this research is descriptive qualitative and the research was conducted for one month starting from August 25 to September 25, 2022. There were 7 informants in this study. The techniques used in this study include: Observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results of this study explain that the values of Islamic education in the Barzanji reading tradition include three aspects, namely aqidah, growing our sense of belief in the Prophet Muhammad that he is the last and most noble Prophet. From the aspect of worship, it includes: The value of Gratitude, namely the expression of gratitude to Allah SWT who has provided sustenance for what has been obtained, The value of friendship, namely the establishment of friendship between religious leaders, the community and the government and to strengthen brotherhood. Moral values: namely morality towards Allah SWT as an attitude or action that should be carried out by humans because humans as servants of Allah SWT should have good morals. Morals to Rasulullah SAW, namely to love and glorify Rasulullah SAW and say blessings and greetings to Rasulullah SAW. The value of mutual help is that it can be applied by providing energy, skills, materials, thoughts, mutual respect and respect